Pelaksanaan Stimulasi Motorik Kasar Anak di Taman Kanak-Kanak Islam Terpadu Ar-Royyan Padang - Zolanda, Putri Attari; Marlina, Serli (TSAQOFAH, 2025)
Gross motor skills are a vital aspect of developmental stimulation in early childhood, contributing significantly to physical maturity and movement coordination. Initial observations indicate that some young children have not yet reached optimal development in this area and still require guidance from teachers. This study aims to describe the implementation of gross motor stimulation activities at Taman Kanak-Kanak Islam Terpadu Ar-Royyan Padang. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The research subjects included teachers and the school principal, with data validity ensured through triangulation techniques. Data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings show that the planning of gross motor stimulation at TK Islam Terpadu Ar-Royyan Padang refers to the Daily and Weekly Learning Implementation Plans (RPPH and RPPM). The stimulation is carried out through a variety of activities such as gymnastics, letter-matching games, bakiak games, dancing, engklek (hopscotch), and swimming. Teachers employ a range of instructional methods, including hands-on practice, performance demonstrations, and learning through play, to stimulate children's gross motor skills effectively. These findings indicate that gross motor stimulation is both structurally designed and variably implemented in accordance with the developmental characteristics of early childhood.